26. PATIENT’S SATISFACTION WITH MEDICAL EXAMINATION AND TREATMENT SERVICES AT SOME MEDICAL STATION AND POLYCLINICS OF SOC SON DISTRICT HEALTH CENTER, HANOI IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the patient’s satisfaction and identify some factors related to patient’ssatisfaction with medical examination and treatment services at some medical stations andpolyclinics at Soc Son district health center, Hanoi in 2023.Subject and method: A cross-sectional study was conducted on 987 patients from June 2023 toJuly 2023.Results: The overall satisfaction rate with medical examination and treatment services of 987patients is 89.9% and there is a relationship between the overall satisfaction rate with gender,education level, travel time, and staff attitudes and medical examination and treatment costs.Conclusion: The patient satisfaction rate with medical examination and treatment services at primaryhealthcare medical facilities is quite high. However, commune health stations and regionalpolyclinics need to continue to take measures to improve patients' access to medical services andorganize training classes for medical staffs to improve the quality of medical services, therebyincreasing people's satisfaction when coming for medical examination and treatment.
Keywords: Soc Son district health center, patient’s satisfaction, medical excamination and treatment services.